PENGARUH KETERAMPILAN METAKOGNISI TERHADAP KEMAMPUAN BERTANYA DAN BERPIKIR KRITIS SISWA SMP - Lia Anggraini; Undang Rosidin; Viyanti - (Jurnal Pembelajaran Fisika, 2013)
The purpose of the research is to determine the influence of metacognition skill towards ability to promote questions and critical thinking skill of junior high school students and the improvement of critical thinking skill. One shot case study design and one group pretest-posttest design have been conducted in the research to obtain the data. By using SPSS 17.0 Program showed that the data distributed normally and linearity. The hypotheses testing used correlation test, simple regression linear, and paired sample t-test. The result of this research showed that: 1) there was a positively and significant influence towards ability to promote questions amounted to 31% and the regressive equation ???? = 37,04 +0,53 ????; 2) there was a positive and significant influence towards critical thinking skill amounted to 24% and the regressive equation ???? = 28,40 +0,54 ????; 3) There is an significantly average improvement in junior high school student’s critical thinking skill caused by the influence of metacognition skill amounted to 22,00 with N-gain average critical thinking skill amounted to 0,70 in high category.Kata kunci: berpikir kritis, kemampuan bertanya, keterampilan metakognisi